The Effect of Selected Demographic Parameters on Intimacy, HIV risk perception and Self-efficacy among Ugandan and Tanzanian University Pre-Service Teachers. - Kobusingye, Loyce Kiiza; Makungu, Bulayi; Namatende-Sakwa, Lydia (Advances in Social Sciences Research Journal, 2020)
The study was conducted among university pre-service teachers pursuing Bachelor of Arts/Bachelor of Science with Education degree programmes, with the major aim of analysing the effect selected demographic attributes or parameters of gender, age and religion on intimacy, HIV risk perception and self-efficacy. A total of 557 respondents selected using systematic random sampling from both Makerere University School of Education (Uganda) and Dar es Salaam University College of Education (Tanzania) were studied and findings revealed that the variation intimacy among the two genders was not significant while the variation in HIV risk perception between the male and female pre-service teachers was significant. It was also observed that the variation in self-efficacy between the two genders was not significant. On the other hand, the, the variation in intimacy between the age cohorts under study was significant while that in HIV risk perception and self-efficacy for the different age groups was not significant. The variations in intimacy, HIV risk perception and self-efficacy between the several religions was found to be non-significant across all religions. The findings therefore point to the need for effective university policies that should incorporate life skills education, HIV workshops, behaviour change programmes, peer education and exemplary leadership.